Absorption coefficients by coloured dissolved organic matter obtained at fixed stations with a Liquid Waveguide Capillary Cell system during HEINCKE cruise HE462 in the North Sea and Sogne Fjord - Astrid Bracher; Yangyang Liu; Sonja Wiegmann; Rüdiger Röttgers (PANGAEA, 2021)
Water samples were taken during the spring (29 April to 7 May 2016) expedition HE462 with RV Heincke in the North Sea and Sogne Fjord. Water samples were collected from CTD Niskin bottles at six different depths from the upper 100 m at 17 Stations. These are the same stations as sampled in Bracher and Wiegmann (2019). Water samples for CDOM absorption analysis are filtered through 0.2 μm filters and analysed onboard with a 2.5-m path length liquid waveguide capillary cell system (LWCC, WPI) following Levering et al. (2017). Details on method adaptation to our instrumentation set-up are provided in Alvarez et al. (2022). Salinity data were extracted from https://doi.pangaea.de/10.1594/PANGAEA.863445.